Emulsifying Characteristics of Gelatin Hydrolysate from Tilapia Skin Covalently Attached with N-hydroxysuccinimide Esters of Fatty Acids - Nurin Imana Hidayati; Retno Indrati; Pudji Hastuti; Masahiro Ogawa (agriTECH, 2020)
This study aims to combine two modification methods, namely enzymatic hydrolysis and covalent attachment with hydrophobic groups, to increase the emulsifying properties of gelatin. The experiment was conducted by using a completely randomized design with three replicates. Enzymatic hydrolysis of gelatin resulted in higher contents of free amino groups, which could be attached to hydrophobic groups. Gelatin hydrolysates covalently attached with the N-hydroxysuccinimide esters of C14:0 and C18:0 fatty acids at a molar ratio of 3.0 showed high emulsifying activity but low stability. Among the samples obtained, gelatin hydrolysate covalently attached with C18:0 at a molar ratio of 3.0 revealed the highest emulsifying activity; however, this sample cannot be considered the best emulsifier among the samples because of its low stability.